Guide to physiotherapy and rehabilitation of cats. Issue 10 (17th December 2021) - Box, Emma
Abstract : Background : Veterinary physiotherapy involves restoring a patient's movement and function following an injury, illness or trauma. In recent years, there has been increasing interest in the application of physiotherapy to small animals; however, it is still often overlooked for cats. Cats are not accustomed to regular handling or restraint and tend to become impatient and bored quickly, which means they are perceived as poor candidates for physiotherapy referral. However, many feline conditions do benefit from rehabilitation. Aim of the article : This article explores the application of physiotherapy techniques to feline patients, highlighting how rehabilitative exercises can be adapted so that they are suitable for cats.